2005
DOI: 10.1157/13078597
|View full text |Cite
|
Sign up to set email alerts
|

Opinión de profesionales y pacientes sobre la introducción de la informática en la consulta

Abstract: The introduction of computers into consultations was accepted well. Professionals were more worried than patients about possible loss of confidentiality, and thought that there had been bigger changes in the doctor-patient relationship and that visits had become longer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 3 publications
1
3
0
Order By: Relevance
“…With respect to the patient-physician relationship, this study reveals the dichotomy between patient and physician perceptions of the interference of EHRs. Similar to previous studies, [8][9][10][11][12][13][14] we found that the majority of patients feel that they are able to maintain good communication and a relationship with their physician in the presence of EHRs. As found in other studies, patient satisfaction remained high with physician EHR usage.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…With respect to the patient-physician relationship, this study reveals the dichotomy between patient and physician perceptions of the interference of EHRs. Similar to previous studies, [8][9][10][11][12][13][14] we found that the majority of patients feel that they are able to maintain good communication and a relationship with their physician in the presence of EHRs. As found in other studies, patient satisfaction remained high with physician EHR usage.…”
Section: Discussionsupporting
confidence: 90%
“…Multiple Choice Questions Correct Answer: The correct answer is option c. Despite the initial negative perceptions of physicians regarding EHR implementation, many studies have shown that EHR implementation leads to improved efficiency, 2 clinician acceptance of the EHR systems, 2,5,8 and overall patient satisfaction. 1,2,[8][9][10][11][12][13][14] However, several studies have found that clinicians are not fully satisfied with EHR systems. Some studies have documented a dichotomy between the perceptions of patients and physicians regarding the impact of EHR systems on patient-physician relationship.…”
Section: Clinical Relevance Statementmentioning
confidence: 99%
See 1 more Smart Citation
“…Physicians' perception of negative impact was not shared by patients who considered that computer use had in general a positive impact on patientphysician communication. Patients' reaction is not surprising, since previous studies on patients' views about the relationship with their doctor regarding the impact of the computer stated that contact with their doctor did not differ significantly [32,38,[46][47][48][49][50]. Nevertheless, concerns about confidentiality were always raised, which did not occur in this study.…”
Section: The Impact Of Computer Use In Clinical Communicationmentioning
confidence: 48%